IMPACT OF NON-FINANCING INCOME ON ISLAMIC BANKING PERFORMANCE: EVIDENCE FROM GCC ISLAMIC BANKS - Muneeb Khalaf Mhaimeed (Scholars Digest Publishing, 2024)
This research examines the impact of non-financial income on performance and risk in 23 Islamic banks in the Gulf Cooperation Council countries from 2011 to 2020, using dynamic econometric data. The results show a noticeable shift towards non-financial income in GCC banks, which prompted a re-evaluation of the benefits and risks of diversification. A significant negative impact on assets (ROA) indicates challenges to returns. However, the correlations with ROE, RAROA, and RAROE were not statistically significant, highlighting the unique structure of Islamic banks. Regarding risk, the non-significant negative relationship between non-finance income and the Z-score indicates a limited impact on the stability of Islamic banks. The study emphasizes the need to consider diverse operating models and regulatory environments when evaluating income diversification strategies in Islamic banks.
Keywords: Non-financing income, Islamic bank performance, GCC countries